The Algorithmic Living Hadith: Prophetic Traditions, Digital Authority, and Muslim Youth Piety in Indonesia - Nur Annisa Istifarin; Syamsudin Syamsudin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Studies of living hadith have largely emphasized local rituals and community-based religious practice, leaving the role of platform algorithms, digital authority, and audience participation in shaping hadith transmission underexplored. This article addresses that gap by examining how hadith is lived through algorithmic mediation among young Indonesian Muslims. Using a qualitative approach based on netnography of hadith-based content on TikTok, Instagram Reels, and YouTube Shorts, the study investigates: (1) how the form and circulation of hadith transform within algorithmic media; (2) how religious authority is negotiated among digital preachers, da'wah influencers, and audiences; and (3) how young Muslims receive, negotiate, and practice hadith encountered on social media. Findings show hadith undergoing an epistemic shift into concise, visual, emotionally resonant content whose visibility algorithms shape more than chains of transmission do. Religious authority becomes increasingly distributed, negotiated through communicative closeness and engagement metrics, at times in tension with sanad-based legitimacy. This mediation shapes youth piety through improved worship, hijrah, and everyday moral conduct, while exposing hadith to the risk of decontextualization. The article proposes algorithmic living hadith as a framework that extends living hadith studies into the digital-algorithmic space, contributing to digital religion scholarship by positioning algorithms as active mediators of religious meaning.